Intimate partner violence related to disclosure of sickle cell disease during pregnancy: evidence from the sickle cell belt of central India - Halim, Nafisa; Patel, Archana; Turan, Janet M.; Shrikhande, Anuradha V.; Kavanagh, Patricia L.; Drainoni, Mari-Lynn; Henderson, David; Anand, Shweta Murali; Agarwal, Nandini; Hibberd, Patricia L. (Frontiers in Global Women's Health, 2025)
BackgroundIntimate partner violence (IPV) negatively impacts pregnant women and their unborn children. Globally, an estimated 19%, 9%, and 6% of women experience psychological, physical, and sexual IPV, respectively, during pregnancy. These rates are higher among pregnant women living with a stigmatizing disease. In this study, we examined the effect of antenatal screening for sickle cell disease (SCD) using the sickle cell solubility test on the risk of IPV among pregnant women in the city of Nagpur in Maharashtra state of India. We hypothesized that a positive solubility test increases the risk of IPV via partner disclosure.MethodsWe conducted a cohort study comparing IPV in 182 pregnant women, before (baseline) and after (endline) having a solubility test. Of the 182 participants, 91 were pregnant women with a positive solubility test and 91 with a negative solubility test. We used the 49-item Indian Family Violence and Control Scale (α = 0.88) to measure IPV and estimated associations using binomial logistic regressions with robust standard errors.ResultsPregnant women with a positive solubility test were at least twice as likely to experience physical, sexual, or psychological IPV as pregnant women with a negative solubility test, even after adjusting for baseline differences between these two groups on common IPV risk factors including the lower level of education and scheduled-caste membership.ConclusionPregnant women who have a positive solubility test are at risk of IPV after following routine instructions to disclose their test results to their male partners, so that they can undergo further testing to determine the baby’s risk of SCD, sickle cell trait, or no risk.ImplicationsIn resource-poor settings with high SCD prevalence, antenatal clinics are increasingly screening pregnant women to prevent mother-to-child transmission of SCD. There is a need to integrate strategies for women to disclose sickle cell screening test results and prevention of IPV caused by male partners.